THE FORMATION OF STUDENTS' CRITICAL THINKING ABILITY THROUGH A SCIENTIFIC APPROACH TO LEARNING AKIDAH AKHLAK CLASS VIII MTS DDI LAPEO CAMPALAGIAN DISTRICT, POLEWALI MANDAR REGENCY - Muhdar, Muhdar; Achruh, Andi; Saprin, Saprin (Program Pascasarjana, UIN Alauddin Makassar, 2022)
The purpose of this study was to describe the application of a scientific approach to learning akidah akhlak for class VII MTs DDI Lapeo, then to describe the formation of students' critical thinking ability in learning akidah akhlak for class VIII MTs DDI Lapeo, as well as to analyze the critical thinking abilities of students in learning akidah akhlak. class VIII MTs DDI Lapeo. The research method used in this research is qualitative. The results of this study indicate that the application of the scientific approach to the learning akidah akhlak for class VIII MTs DDI Lapeo has been implemented properly in accordance with the five stages of the scientific approach. As for the formation of students' critical thinking abilities in these five stages, The activity of observing students is directed to analyze and formulate problems. In the activity of asking questions, students are facilitated to make questions. Exploring activities, students are directed to collect information related to the material. In reasoning activities, students are facilitated to process the information received. In networking activities, students are directed to convey opinions and solutions in response to the formulation of problems that are made. Meanwhile, the critical thinking ability of class VIII students of MTs DDI Lapeo after applying the scientific approach is the ability to analyze and formulate a problem, provide ideas, assess the truth of information received, accept or be open to other people's opinions, solve problems on a problem, know the essence of learning akidah akhlak, analyzing the information received, and making questions and answering questions about akidah akhlak lessons. The implication of this research is that the scientific approach is a scientific approach that is very supportive in shaping the critical thinking abilities of students, because it focuses on the activeness of students, so that learning does not occur in one direction.